Non-Pharmacological Interventions For Pain Management In Post-Sectio Casearea Mothers: Literature Review - Mamuroh, Lilis; Sukmawati, Sukmawati; Nurhakim, Furkon (Universitas Aisyah Pringsewu, 2024)
Background: Pain is an unpleasant emotional and sensory experience associated with potential and actual tissue damage. Pain can also be felt by post partum mothers with post caesarean section (SC). There are various ways to relieve pain in post partum mothers with post caesarean section that can be done. Purpose: The aim of this evidence-based practice is to compare several non-pharmacological methods for pain management in post-caesarean mothers. Methods: The research design used a literature review or literature review using international sources. Literature search for data collection used Proquest, Pubmed, Sciencedirect, and Science Publishing Group databases. After going through the selection, 7 articles were obtained which were then selected using PICO, inclusion criteria, and exclusion criteria. Result: Post-caesarean section pain management can be done in various ways including using lavender aromatherapy, reiki applications, benson relaxation techniques, and massage techniques that can reduce the level of pain in post-caesarean surgery mothers. Conclusion: The pain management techniques used could effectively reduce the level of pain in post-caesarean mothers.